Towards a circular economy in lithium ion battery recycling by integrating microbial processes with electrowinning and precipitation for sustainable metal recovery - Baniasadi, Mahsa; Upvan, Kumar; Pourhossein, Fatemeh; Graves, John E.; Latvyte, Egle; Farnaud, Sebastien (Elsevier, 2025)
With increased use of Lithium-Ion Batteries (LIBs) and the scarcity of some of their components, their recycling and the recovery of their metals have become essential. In this work, an indirect bioleaching process was designed to solubilise metals from LIB black mass using biogenic acid generated in a stirred tank bioreactor. The biogenic acid was used in addition to H2O2 as a reductant for improved solubilisation, and influential factors including pulp density, temperature, and concentration of H2O2 were optimised. The best results were achieved at 55 °C, with a pulp density of 7.5% (w/v) and 0.5% (v/v) H2O2, which resulted in 82% Li, 32% Ni, 24% Co and 21% Mn solubilisation in 5 min of the process. However, over time transition metals in the leachate did not remain in solution, due to their adsorption onto the carbon content of the black mass. To selectively recover solubilized Co, Ni, Mn, and Li from the leachate, a combined process of electrowinning and precipitation was applied to the leachate, leading to the successful electroplating of Co, Ni and Mn with 100%, 100% and 97.2% of solubilised metals respectively, while 40% of the Li was recovered by precipitation following the addition of sodium carbonate. These results constitute a promising step toward closing the loop for the sustainable selective recovery of critical metals used in LIB manufacturing and suggest the next targets to improved bioleaching efficiency.
Keywords: Lithium-ion batteries (LIBs); Bioleaching; Electrowinning; Circular economy; Precipitation; 40 Engineering; 34 Chemical Sciences; 3406 Physical Chemistry; 12 Responsible Consumption and Production; Environmental Sciences; Ions; Lithium; Metals; Electric Power Supplies; Recycling